KLASIFIKASI PENYAKIT PARU BERDASARKAN CITRA X-RAY THORAX MENGGUNAKAN METODE FRAKTAL BOX COUNTING - Beny My Sapata; Dwi Juniati (MATHunesa: Jurnal Ilmiah Matematika, 2019)
The lungs are important and vital organs that are easily infected. Lung examination can be done through examination of x-ray images, but the clinical diagnosis of the results of x-ray images is difficult. In making it easier to analyze the diagnosis of the results of the x-ray image, this research carried out the process of classifying x-ray images based on the type of disease.. The image that was processed was 120 (one hundred and twenty) chest x-ray images by segmenting the lung area. From this lung area, then canny edge detection is done to take spots from lung disease. From smart fractal edge detection values are obtained, which will be calculated using the box calculation method, so classification can be done. The results of the experiment using the nearest k-neighbor method (K-NN), where the results with the greatest accuracy are shown by the value K = 5 which is 79.65% and the lowest accuracy at the value K = 7 is 71.28%.